A rare case of Merkel cell carcinoma with ovarian metastasis - Nicole Keller; Beatrix Haemmerle; Seraina Schmid (Elsevier, 2019)
Introduction: Merkel cell carcinoma (MCC) is a rare cutaneous malignancy that normally occurs in sun-exposed areas of the skin. Risk factors are immundeficency and Merkel cell polyomavirus.Treatment options are surgery, radiotherapy, chemotherapy and immunotherapy in clinical trials. Case report: We describe a case of an 80-year-old woman with ovarian metastasis of MCC six years after excision of a cutaneous MCC on the cheek. Discussion: To our knowledge only three cases with ovarian metastasis of MCC have been described so far. Our case is the second with distant metastasis to the ovary spreading from a primary tumor in the skin of the head, in the other two cases the primary tumor was in the inguinal skin. Conculsion: MCC is a highly aggressive cutaneous and mucosal malignancy with frequent recurrence, lymph node and distant metastases. There is no clear consensus how to treat metastatic disease. Keywords: Merkel cell carcinoma (MCC), Ovarian metastases, Cutaneous malignancy, Gynecological malignancy